On the issue of categorization of objects of critical information infrastructure of seaports - Kristina V. Natashova; Sergey S. Sokolov; Oleg N. Gubernatorov; Anatoliy P. Nyrkov; Anton V. Kirikov (Безопасность информационных технологий, 2020)
The purpose of the article is to consider the problematic issues that arise during the categorization of CII objects. Seaports are of strategic importance for the development of the Russian Federation's economy and transport support for foreign trade. In accordance with Federal law No. 187-FZ of July 26, 2017 "on security of critical information infrastructure of the Russian Federation", seaports are subjects of CII in the field of transport. Compliance with the requirements of this law, in particular, addressing issues related to the categorization of CII objects in accordance with Russian Government Resolution No. 127 of February 8, 2018 "on approval of the rules for categorizing critical information infrastructure objects of the Russian Federation, as well as the list of indicators of the criteria for the significance of critical information infrastructure objects of the Russian Federation and their values", requires careful study and evaluation, because, that CI subjects are increasingly faced with the complexity of processes and the need to take into account the specifics of a particular area of their activities. This article considers the subject of the Kaliningrad commercial sea port CII and categorizes one of the information systems as the author's recommendations for the implementation of the Decree of the Government of the Russian Federation No. 127 of February 8, 2018 for information systems of seaports. In conclusion, the authors note the importance of developing industry regulations for categorizing and ensuring the security of CII, the importance of developing standard models of violators that would take into account industry characteristics, and the need to attract narrowly focused specialists to the work of the Commission, both from the organization and from outside.